Temporal Biomarker Profiling Reveals Longitudinal Changes in Risk of Death or Myocardial Infarction in Non–ST-Segment Elevation Acute Coronary Syndrome. (6th January 2020) - Chan, Mark Y; Neely, Megan L; Roe, Matthew T; Goodman, Shaun G; Erlinge, David; Cornel, Jan H; Winters, Kenneth J; Jakubowski, Joseph A; Zhou, Chunmei; Fox, Keith A A; Armstrong, Paul W; White, Harvey D; et al.
Abstract: BACKGROUND: There are conflicting data on whether changes in N-terminal pro–B-type natriuretic peptide (NT-proBNP) and high-sensitivity C-reactive protein (hs-CRP) concentrations between time points (delta NT-proBNP and hs-CRP) are associated with a change in prognosis. METHODS: We measured NT-proBNP and hs-CRP at 3 time points in 1665 patients with non–ST-segment elevation acute coronary syndrome (NSTEACS). Cox proportional hazards was applied to the delta between temporal measurements to determine the continuous association with cardiovascular events. Effect estimates for delta NT-proBNP and hs-CRP are presented per 40% increase as the basic unit of temporal change. RESULTS: Median NT-proBNP was 370.0 (25th, 75th percentiles, 130.0, 996.0), 340.0 (135.0, 875.0), and 267.0 (111.0, 684.0) ng/L; and median hs-CRP was 4.6 (1.7, 13.1), 1.9 (0.8, 4.5), and 1.8 (0.8, 4.4) mg/L at baseline, 30 days, and 6 months, respectively. The deltas between baseline and 6 months were the most prognostically informative. Every +40% increase of delta NT-proBNP (baseline to 6 months) was associated with a 14% greater risk of cardiovascular death (adjusted hazard ratio (HR) 1.14, 95% CI, 1.03–1.27) and with a 14% greater risk of all-cause death (adjusted HR 1.14, 95% CI, 1.04–1.26), while every +40% increase of delta hs-CRP (baseline to 6 months) was associated with a 9% greater risk of the composite end point (adjusted HR 1.09, 95% CI, 1.02–1.17) and a 10% greater risk of myocardial infarction (adjusted HR 1.10, 95%, CI 1.00–1.20). CONCLUSIONS: Temporal changes in NT-proBNP and hs-CRP are quantitatively associated with future cardiovascular events, supporting their role in dynamic risk stratification of NSTEACS. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov identifier NCT00699998